Creating the Illusion a fashionable history of Hollywood costume designers - Jorgensen, Jay 1964-; Scoggins, Donald L. (Running Press, 2015)
Marilyn Monroe made history by standing over a subway grating in a white pleated halter dress designed by William Travilla. Hubert de Givenchy immortalized the Little Black Dress with a single opening scene in Breakfast at Tiffany's. A red nylon jacket signaled to audiences that James Dean was a Rebel Without a Cause. For more than a century, costume designers have left indelible impressions on moviegoers' minds, yet until now, so little has been known about the designers themselves and their work to compliment and enrich stories through fashion. Hollywood Costume Design presents the history of fashion on film, showcasing not only classic moments from film favorites, but a host of untold stories about the creative talent working behind the scenes to dress the stars from the silent era to the present day
Keywords: Kostümbildner; Design; Kostümbildnerin; Kostüm; Mode; Filmausstattung; Los Angeles- Hollywood; Costume designers / United States / Biography; Fashion designers / United States / Biography; Fashion in motion pictures; Costume design / United States / History; Costume designers / Biography / United States; Fashion designers / Biography / United States; Costume design / History / United States